Comparative Metaphysics and Theology as a Scientific Endeavor A Ruist (Confucian) Perspective - Song, Bin (2019)
Understood as being nothing more than fallible assumptions about the boundary conditions of an inquisitive worldview, this article seeks to argue that metaphysics and theology can, in fact, be pursued as a scientific endeavor. If we broaden our understanding of how perceived realities furnish feedback in order to refine preestablished human discourses, Ruist (Confucian) metaphysics and theology especially can be recognized as being historically pursued as a science by its own right. Eventually, the distinction of Western and Ruist traditions of metaphysics and theology, as well as the imperfections in each of them, speaks to the need of mutual learning for constructing a more robust metaphysical worldview in the twenty-first century.